2017
DOI: 10.1371/journal.pone.0178329
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1-like peptide is a novel metabolic factor that suppresses feeding, and regulates whole-body energy homeostasis in male Wistar rats

Abstract: Nucleobindin-1 has high sequence similarity to nucleobindin-2, which encodes the anorectic and metabolic peptide, nesfatin-1. We previously reported a nesfatin-1-like peptide (NLP), anorectic in fish and insulinotropic in mice islet beta-like cells. The main objective of this research was to determine whether NLP is a metabolic regulator in male Wistar rats. A single intraperitoneal (IP) injection of NLP (100 μg/kg BW) decreased food intake and increased ambulatory movement, without causing any change in total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…For testing the effects of NESF or NLP on GH, cells at 90% of confluence were used. The growth culture media was supplemented with rat NESF (custom synthesized peptide 6 , > 95% purity, ABGENT, USA) or rat NLP (custom synthesized peptide 7 , > 95% purity, ABGENT) at 0 (Control), 0.001, 0.01, 0.1, 1, 10, 100 or 1000 nM concentration and cells were incubated for 1, 6 or 24 h. The 24 h time point was chosen as previous studies with the same cell lines reported mRNA changes at that time 38 , 39 . After incubation, cells were washed twice with 1X PBS before the collection of total RNA or the protein content, as explained below.…”
Section: Methodsmentioning
confidence: 99%
“…For testing the effects of NESF or NLP on GH, cells at 90% of confluence were used. The growth culture media was supplemented with rat NESF (custom synthesized peptide 6 , > 95% purity, ABGENT, USA) or rat NLP (custom synthesized peptide 7 , > 95% purity, ABGENT) at 0 (Control), 0.001, 0.01, 0.1, 1, 10, 100 or 1000 nM concentration and cells were incubated for 1, 6 or 24 h. The 24 h time point was chosen as previous studies with the same cell lines reported mRNA changes at that time 38 , 39 . After incubation, cells were washed twice with 1X PBS before the collection of total RNA or the protein content, as explained below.…”
Section: Methodsmentioning
confidence: 99%
“…During proteolytic processing of NUCB2 two inactive derivatives: nesfatin 2 and 3 are also created (Oh-I et al 2006). Interestingly, its sister protein nucleobindin-1 (NUCB1) is a precursor of another very weakly studied neuropeptide called nesfatin-1-like peptide (NLP) that also has anorexigenic properties in animals (Gawli et al 2017). Nesfatin-1 has a highly conserved molecular structure which is characterized by a distinct sequence homology between mammals including human, and the lower vertebrate species (Gonzales et al 2010).…”
Section: Neuropeptides In the Mechanisms Of Anorexia Nervosamentioning
confidence: 99%
“…The presence of NLP was reported in tissues were NUCB2/NESF-1 was previously identi ed, including pancreas, pituitary, gonads, and gut [12,13]. Similarly, NLP was shown to suppress food intake and modulate the expression of appetite-regulatory hormones in gold sh [13] and rats [14].…”
Section: Introductionmentioning
confidence: 88%
“…324911] attached to a 27G needle in the lower right quadrant of abdomen to avoid damage to internal organs. The selected dose was validated in a previous study [14]. After 30 min, mice were euthanized, and blood samples and internal organs were collected.…”
Section: Intraperitoneal Nlp Injection In Wildtype Mice and Nucb1 Kno...mentioning
confidence: 99%